EFFECTS OF PROBLEM-SOLVING AND GUIDED INQUIRY STRATEGIES ON SENIOR SECONDARY STUDENTS’ LEARNING OUTCOMES IN BIOLOGY IN IBADAN (2016)
Biology is a very important science subject offered by students in senior secondary schools. Students’ performance in the subject has been reported as poor. Various instructional strategies have been used without much improvement in students’ achievement and demonstration of practical skills. Studies have shown that teacher-centred techniques employed over the years did not yield desired result. This study examined the effects of problem-solving and guided inquiry instructional strategies on students’ achievement and practical skills in Biology. The study also examined the moderating effects of career aspiration and gender. The study was guided by the theory of constructivism. The pretest-posttest control group quasi-experimental design using a 3x2x2 factorial matrix was adopted. Multistage sampling procedure was employed. Two Local Government Areas were randomly selected from the existing two clusters of Ibadan educational zones. Three schools were purposively selected from each Local Government area with consideration for type of school and functional laboratory. Two schools were randomly assigned to each of experimental and control groups. Two hundred and forty students participated in the study. Instruments used were Biology Achievement Test (r = 0.78), Test of Practical Skills (r = 0.82), Career Aspiration Interest Scale (r = 0.78) and Instructional Guides. Data were analysed using descriptive statistics, Analysis of Covariance and Sidak post-hoc test at 0.05 level of significance. The results showed that there was a significant main effect of treatment on students’ achievement (F(2,228) = 9.69; partial Ƞ2 = .07) and students’ practical skills (F(2,228) = 66.38; partial Ƞ2 = .36) in Biology. Students in the guided inquiry group had the highest mean score ( = 15.09) followed by those in problem-solving ( = 12.78) and demonstration ( = 11.62). The highest mean scores in practical skills was obtained by those in guided inquiry ( = 53.25) followed by those in problem-solving ( = 52.48) and demonstration ( = 33.31) groups. There was a significant effect of career aspiration on students’ practical skills (F(2,228) = 4.33; partial Ƞ2 = .02) but not on achievement. Students in the biological science had higher mean score ( = 48.49) than their counterparts in physical science ( = 42.27). There was interaction effect of treatments and career aspiration on students’ achievement (F(2,228) = 3.43; partial Ƞ2 = .03) but not on practical skills. Participants in biological science had higher mean score ( = 16.76) than their counterparts in physical science ( = 13.42), when guided inquiry strategy was used. There was significant interaction effects of treatment, career aspiration and gender on students achievement (F(2,228) = 4.27; p partial Ƞ2 =.02) but not on practical skills. Male biological science students in guided inquiry group had higher mean score ( = 16.85) than their female counterparts ( = 16.66). Guided inquiry strategy was the most effective in improving female students’ achievement and practical skills demonstration in biological science. Teachers should be encouraged to use guided inquiry strategy in teaching biology among female students